CARDIO-FIT - Nichols, Emma Hitt (MD Conference Express, 2015)
The prospective CARDIO-FIT study shows that a structured exercise program that results in gains in cardiorespiratory fitness significantly improves freedom from atrial fibrillation and arrhythmia-free survival among obese patients with atrial fibrillation. In addition, weight loss with or without improvement in cardiorespiratory fitness improves freedom from atrial fibrillation and arrhythmia-free survival.